Feeding Pellets Containing Agro-Industrial Waste Enhances Feed Utilization and Rumen Functions in Thai Beef Cattle - Natdanai Kanakai; Sawitree Wongtangtintharn; Chanon Suntara; Anusorn Cherdthong (Animals, 2023)
The objective of this research was to investigate the effects of citric waste fermented with yeast waste pellet (CWYWP) supplementation on feed intake, rumen characteristics, and blood metabolites in native Thai beef cattle that are fed a rice-straw-based diet. Four native male Thai beef cattle (1.0–1.5 years old) with an initial body weight (BW) of 116 ± 16 kg were held in a 4 × 4 Latin square design within 21-day periods. The animals were assigned to receive CWYWP supplementation at 0%, 2%, 4%, and 6% of the total dry matter (DM) intake per day. The results indicate that feeding beef cattle with CWYWP leads to a linear increase in the total intake as well was the intake of crude protein (CP) and the digestibility of CP, with the maximum levels observed at 6% CWYWP supplementation (p < 0.05). Rumen characteristics, including pH, blood urea-nitrogen concentration, and protozoal population, showed no significant alterations in response to the varying CWYWP dosages (p > 0.05). In addition, the CWYWP supplementation resulted in no significant changes in the concentration of ammonia-nitrogen, remaining within an average normal range of 10.19–10.38 mg/dL (p > 0.05). The inclusion of 6% CWYWP resulted in the highest population of ruminal bacteria (p < 0.05). Additionally, the CWYWP supplementation led to a statistically significant increase in the mean propionic acid concentration as compared to the group that did not receive the CWYWP supplementation (p < 0.05). In conclusion, this experiment demonstrates that supplementing Thai native beef cattle with CWYWP at either 4% or 6% DM per day can enhance their total CP intake as well as the CP digestibility and rumen bacterial population, and can increase propionate concentration.